Downregulation of DAB2IP results in cell proliferation and invasion and contributes to unfavorable outcomes in bladder cancer. Issue 6 (8th May 2014) - Shen, Yi‐Jun; Kong, Zhao‐Lu; Wan, Fang‐Ning; Wang, Hong‐Kai; Bian, Xiao‐Jie; Gan, Hua‐Lei; Wang, Chao‐Fu; Ye, Ding‐Wei
<x xml:space="preserve">Abstract</x> The DOC‐2/DAB2 interactive protein (DAB2IP) is a member of the Ras GTPase‐activating protein family. It has been shown to be often downregulated and a poor prognostic factor in several human malignancies. In this study, we analyzed the clinicopathological features and outcomes of DAB2IP expression in 135 patients with urothelial carcinoma of the bladder (UCB) treated by radical cystectomy plus bilateral lymph node dissection, and evaluated the effect of DAB2IP knockdown in vitro using the MTT method, colony formation assay, cell cycle assay, and cell migration and invasive assay. We found low expression of DAB2IP was significantly associated with high pathological stage (P = 0.002), high pathological grade (P = 0.02), tumor size more than 3 cm (P = 0.04), and presence of histological variants (P = 0.01). DAB2IP was an independent prognostic factor of disease recurrence (hazard ratio, 2.67; P = 0.034) and cancer‐specific survival (hazard ratio, 2.79; P = 0.038). Knockdown of DAB2IP could promote cell proliferation, migration, and invasion. Downregulation of DAB2IP could activate the ERK and Akt pathways and was correlated with the expression of epithelial–mesenchymal transition markers, such as E‐cadherin and vimentin. In conclusion, downregulation of DAB2IP is associated with features of biologically aggressive UCB and results in cell proliferation, migration, and invasion of bladder cancer. DAB2IP may serve as a promising biomarker in patients with UCB treated by radical cystectomy and bilateral lymph node dissection.